Study of the high energy neutron flux (15-20 MeV) using a BC501A liquid scintillator - Mitsi, E.; Chasapoglou, S.; Kalamara, A.; Kokkoris, M.; Michalopoulou, V.; Stamatopoulos, A.; Vlastou, R.; Lagoyannis, A.; Eleme, Z.; Patronis, N. (HNPS Advances in Nuclear Physics, 2019)
An experiment was conducted in order to characterize the neutron beam between ~15-20 MeV, at the 5.5 MeV tandem T11/25 Accelerator of NCSR ‘‘Demokritos’’. A liquid scintillator, BC501A, was used due to its n-γ discrimination capability and a versatile pulse shape analysis was applied. Offline, the discrimination circuit was tested for tolerance in high counting rates and sensitivity in lowering the limit of the neutron energy monitored through the threshold of the processed signal. The employed circuit proved to be very sensitive to changes in the latter. Neutron spectra at the energies of 14.8, 16.6, 19.2 and 20 MeV were acquired and the unfolding process using the DIFBAS code is currently in progress. Their deconvolution is expected to reveal the extent of the presence of low-energy parasitic neutrons.